The Effectiveness of Six-Week Balance Training with Perturbation Intervention in Enhancing Dynamic Balance of Basketball Players - Lee, Ai Choo; Sankaravel, Mohansundar; Chen, Zhee Xuen (Physical Education Theory and Methodology, 2023)
Background. It is known that all sports require dynamic balance and more specifically towards contact sports such as basketball which puts players through array of perturbation and collision during the game. The purpose of this study was to find out the effectiveness of six-week balance training with perturbation in enhancing dynamic balance of basketball players. Materials and methods. The study participants were ten basketball players who volunteered and were randomly distributed into an Experimental Group (N=5) and a Control Group (N=5). The Experimental Group received a six weeks balance training intervention with perturbation for a total of 18 sessions, while Control Group kept regular training. The Y-balance test was used in pre-test and post-test to measure dynamic balance of both groups. Independent sample t-test was used for the analysis of results. Results. The study findings revealed that the Experimental Group improved significantly in dynamic balance at p=0.000 after having undergone the 18 sessions of intervention with perturbation, while there was no significant improvement in the Control Group. Conclusions. This study concluded that the six-week balance training with perturbation is effective in enhancing dynamic balance control in basketball players. This intervention can be modified or integrated into a neuromuscular training program to further improve dynamic balance of basketball players, hence, may help in reducing injury risk. This intervention also can be suggested as a training regime for other contact sports that require excellent balance control.